VISUALISASI ELEMEN PEMBENTUK CONSUMER BRANDSCAPE MELALUI OPOSISI BINER SEMIOTIKA PEMASARAN XING FU TANG (幸福堂) DAN XI BO BA (喜悦) - Gandakusumah, Beryl; Marta, Rustono Farady (Jurnal Bahasa Rupa, 2021)
The use of visual elements based on color, texture, and shape in semiotics is known as a sign or symbol. The strength of the use of these elements is driven by the consumer brandscape which consists of several elements. The adoption of creative strategies by the two brands is an effort made by XING FU TANG (幸 福 堂) and XI BO BA (喜悦) in promoting and instilling their brand ideology to consumers. This research is comparative in nature through the Binary Opposition Strategy in Oswald's Semiotic Marketing Method, in order to be able to trace the two brands from the perspective of the consumer brandscape with a qualitative approach. The results obtained show that XING FU TANG (幸福 堂) uses elements of classical oriental nuances, while XI BO BA (喜悦) defines its brand to target modern and contemporary circles. The application of marketing semiotics is carried out by the two brands through visual elements and is a form of the consumer brandscape which consists of a combination of cultural, emotional, and conical aspects of a sign.